2012
DOI: 10.2105/ajph.2011.300220
|View full text |Cite
|
Sign up to set email alerts
|

Physical Education, Obesity, and Academic Achievement: A 2-Year Longitudinal Investigation of Australian Elementary School Children

Abstract: The attenuated age-related increases in percentage of body fat and enhanced numeracy development among elementary school children receiving PE from specialists provides support for the role of PE in both preventive medicine and academic development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
81
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 24 publications
2
81
1
5
Order By: Relevance
“…Indeed, we have previously reported beneficial effects of the SPE program on blood lipids, (37) insulin resistance, (11) percent body fat, and academic performance. (12) A further limitation of this study relates to our inability to precisely quantify the PE conducted by the classroom teachers. Recent observations in this jurisdiction suggests that PE and sport delivered by classroom teachers does not meet curriculum requirements; in effect our control group may have received less PE than they reported.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, we have previously reported beneficial effects of the SPE program on blood lipids, (37) insulin resistance, (11) percent body fat, and academic performance. (12) A further limitation of this study relates to our inability to precisely quantify the PE conducted by the classroom teachers. Recent observations in this jurisdiction suggests that PE and sport delivered by classroom teachers does not meet curriculum requirements; in effect our control group may have received less PE than they reported.…”
Section: Discussionmentioning
confidence: 98%
“…The present study supported this finding, which showed that watching TV more than three hours in a day was significantly associated with the high BMI. The possible explanations could be that the screen time may displace more active pursuits, advertising of junk food and fast food increases children's requests for those particular foods and products, snacking increases while watching TV or movies, and late-night screen time may interfere with getting adequate amounts of sleep, which is a known risk factor for obesity (Telford et al, 2012). This finding was in agreement with a recent study conducted in Saudi Arabia, which revealed that the prevalence of obesity among the school children was increased with increase in hours of watching TV (El Mouzan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Based on experience working with policymakers, one of the first questions they are likely to ask when presented with the data used by the authors is Bdoes this mean these children are more physically active?^It would be beneficial to know if an increase in physical education time translates into an increase in the amount of physical activity participated in during PE, the school day, and perhaps even across the week. There is evidence to support that it does [9] and that this does not jeopardize academic achievement [10,11]. Including such evidence would further strengthen the case for greater mandating of PE.…”
Section: Discussionmentioning
confidence: 93%
“…While intuitively this may seem the case, supporting evidence would be helpful to include given that there would be a resource cost associated with implementing such a policy and policymakers would want such evidence. Again, there are studies that support this [9,11,14,15]. Providing training is an important way of up-skilling current teachers but more evidence is needed around the minimum dose of professional development required to have an impact on child activity levels.…”
Section: Discussionmentioning
confidence: 99%